Factors Affecting Community Economic Welfare In Tongko Village, Baroko District, Enrekang Regency - Ernawati Ernawati (Income Journal Of Economics Development, 2022)
This study aims to analyze the effect of gross income on the welfare of the community in Tongko Village, Baroko District, Enrekang Regency. The type of research used in this research is case study research with a quantitative descriptive approach. The processed data is a summary of the value of income and education to the value of community welfare obtained from the annual report (Annual Report) of the Tongko village office. The calculation technique used in research is to calculate the multiple linear regression . Research results show that income and education variables have a positive and significant impact on the economic welfare of the community in Tongko Village, Baroko District, Enrekang Regency.